Diagnostic and prognostic values of conjunctival and oral biopsies analyzed by direct immunofluorescence in patients with mucous membrane pemphigoid - Jakubowska, Beata; Pietrzyk, Ewelina; Maciejewicz, Piotr; Kowalewski, Cezary; Wozniak, Katarzyna (Frontiers in Medicine, 2023)
Mucous membrane pemphigoid (MMP) is diagnosed on the basis of a characteristic clinical picture (a predilection for mucosal involvement and scarring in the affected tissues) and a positive direct immunofluorescence (DIF) result . Here, we compare diagnostic and prognostic value of conjunctival and oral biopsy analyzed by DIF in patients with MMP. Sixteen patients with MMP and mucosal involvement as a predominant symptom were classified into 3 groups based on the clinical picture. Oral and conjunctival DIF were performed in all patients. Our study showed that patients with simultaneous oral and conjunctival involvement had oral DIF positive in 83% and ocular DIF positive in 100%. Patients with isolated ocular MMP had oral DIF positive in 50%, and ocular DIF positive in 66%. Patients with only oral involvement MMP had oral DIF positive in 100%, and ocular DIF positive in 50%. Oral biopsy should be taken as a first and is usually sufficient for the diagnosis, even in patients with exclusively ocular MMP, whereas in patients without clinical ocular involvement ocular DIF is positive in half of the cases and may be a predictive factor for ocular lesions in the future.